Predictive value of MCM5 (ADXBLADDER) analysis in urine of men evaluated for the initial diagnosis of bladder cancer: A comparative prospective study. Issue 11 (20th June 2020) - Anastasi, Emanuela; Maggi, Martina; Tartaglione, Sara; Angeloni, Antonio; Gennarini, Giuseppina; Leoncini, Pier Paolo; Sperduti, Isabella; Di Lascio, Giovanni; De Stefano, Virgilio; Di Pierro, Giovanni Battista; Del Giudice, Francesco; Busetto, Gian Maria; et al.
Abstract: Background: To compare predictive value of MCM5 to urinary cytology (UC) for the primary diagnosis of bladder cancer (BCa). Methods: We prospectively enrolled 91 patients who presented macroscopic hematuria or persistent lower urinary tract symptoms at our institution. Single voided mid‐stream urine specimens were collected for UC and MCM5 (ADXBLADDER; Arquer Diagnostics Ltd, Sunderland, United Kingdom) assessment. Cystoscopy was used as confirmatory test, and positive cases underwent transurethral resection of bladder tumor with histopathological evaluation. Results: Forty cases (43.9%) showed a positive cystoscopy for BCa. Histology was obtained in 37 cases: 16 (43.2%) high‐grade (HG) and 21 (56.8%) low‐grade (LG) transitional cell carcinoma (TCC). UC had a sensitivity of 62.5%, specificity of 86.3%, PPV of 78.1% and NPV of 74.6%. Sensitivity, specificity, PPV and NPV of MCM5 were 60.0%, 88.2%, 80.0% and 73.8%, respectively. According to tumor grade, MCM5 and UC showed a sensitivity of 47.6% and 52.4% in LG, and 87.5% and 75.0%, respectively, in HG TCC. False‐positive rates were 11.8% and 13.7% of negative cases for BCa with MCM5 and UC test, whereas false‐negative results were found in 40.0% and 37.5% of BCa cases, respectively. The combination of the two tests showed a sensitivity of 71.4% in LG, and 93.8% in HG TCC. Conclusion: In the present analysis, MCM5 showed lower sensitivity than UC in predicting BCa primary diagnosis. According to tumor grade, MCM5 showed a higher sensitivity in the detection of HG BCa compared to UC, although values were not significantly different.